Perancangan Set Furnitur dengan Pendekatan Fashion Brand Chanel - Celvin Anlenxia (Intra, 2017)
At this time, a lot of socialite from the middle-upper class of society who can buying branded stuffs. Many fashion houses that release furniture collection with their well-known brand and otherwise a lot of furniture designer collaboration with fashion houses. The design of this furniture takes Chanel brand because Chanel is one of brand in this world that has been long enough in the fashion industry and has given a lot of influences in the fashion world. In addition, Chanel has not release furniture collection or work together with furniture designer to design a furniture collection. This design is using design thinking method. The concept that used in this design is majestic geometrical in which majestic is chosen to represent fashion, and geometrical is chosen to give a simple impression. Therefore, with this design it will enlarge opportunities to enhance and expand Chanel's marketplace in business market competition.